The Impact of Wastewater Discharge and Agriculture on Water Quality and Nutrient Retention of Namatala Wetland, Eastern Uganda - Namaalwa, Susan; van Dam, Anne A.; Gettel, Gretchen M.; Kaggwa, Rose C.; Zsuffa, István; Irvine, Kenneth (Frontiers in Environmental Science, 2020)
The Namatala Wetland in Uganda faces severe degradation from agricultural development and urbanization. Besides the Namatala River and tributary rural streams, the wetland receives surface water from Mbale town and wastewater from two sets of wastewater stabilization ponds. The objective of this study was to examine water quality, and sediment and nutrient retention in different land use zones. Five hydrogeomorphic units (HGMUs) were distinguished on the basis of soil, hydrology and land use. HGMUs 1 and 2 in the upstream part of the wetland are characterized by drainage channels and mixed agriculture. HGMU 3 is a wet floodplain with intensive rice farming. HGMU 4 and 5 are permanently wet units in the downstream part of the wetland with moderate rice farming and partly intact papyrus (Cyperus papyrus L.) vegetation. Stream discharge was measured, and surface water samples collected, monthly from the river channel, the tributaries, and the five HGMUs from April 2015 to October 2016. Significant differences in total nitrogen (TN), phosphorus (TP) and total suspended solids (TSS) were observed among the streams and among the five HGMUs, with highest concentrations in urban streams and lowest in the main river channel and rural streams. Among the HGMUs, nutrients and TSS were highest within HGMU 3 and lowest in HGMU 1 and 5. Loads of nutrients and sediment into the wetland were greater from the main river channel compared with urban and rural streams. Regressions of net TN, TP and TSS yields for each HGMU against river discharge showed a net loss of nutrients and sediments in HGMU 3 with the most intensive agriculture, and net retention in HGMUs 4 and 5 which mostly maintain their wetland character. This study shows that sediment and nutrient retention in the downstream part of the wetland compensate for increased export caused by agricultural and urban land use in the middle and upper zones of the wetland, thus maintaining net nutrient retention of Namatala Wetland. However, there is a trade-off between economic development and wetland protection and future management planning should incorporate more sustainable farming practices and improved wastewater treatment.